2014
DOI: 10.1021/jp502144u
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Hydride Modification on Hydrazine Borane for Improved Dehydrogenation

Abstract: Hydrazidotrihydridoborates of various alkali metals, i.e., NaN2H3BH3 and KN2H3BH3, were synthesized successfully via a liquid approach. The crystal structures of NaN2H3BH3 and KN2H3BH3 were determined, and their dehydrogenation properties were compared with LiN2H3BH3 and N2H4BH3. A clear correlation between sizes of metal cations in hydrazidotrihydridoborates and their corresponding melting and dehydrogenation temperatures was observed. The dehydrogenation temperature was found dependent on the melting tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…This is illustrated in Figure 6 where a mechanism of decomposition is suggested on the basis of both the present results and the results reported for LiN 2 H 3 BH 3 elsewhere [8]. A polymeric product of unknown composition forms, similar to the residues recovered upon the dehydrogenation of most of the B–N–H compounds [5,6,7,8,9,10,11,12,27]. The nature of such residues is unknown yet because of their difficult characterization (amorphous to X-ray and too complex composition for FTIR and NMR spectroscopy techniques).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 75%
See 1 more Smart Citation
“…This is illustrated in Figure 6 where a mechanism of decomposition is suggested on the basis of both the present results and the results reported for LiN 2 H 3 BH 3 elsewhere [8]. A polymeric product of unknown composition forms, similar to the residues recovered upon the dehydrogenation of most of the B–N–H compounds [5,6,7,8,9,10,11,12,27]. The nature of such residues is unknown yet because of their difficult characterization (amorphous to X-ray and too complex composition for FTIR and NMR spectroscopy techniques).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 75%
“…The enthalpy of reaction of KH with N 2 H 4 BH 3 was measured as being −70,247.2 J mol −1 . Accordingly, the safest way to get potassium hydrazinidoborane KN 2 H 3 BH 3 is by wet synthesis (i.e., suspension in tetrahydrofuran) in an autoclave reactor [11]. All of these alkali hydrazinidoboranes have shown better and safer dehydrogenation properties than the parent hydrazine borane.…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, we found that the solid-state reaction between potassium hydride and hydrazine borane is extremely reactive in inert and room conditions, even more reactive than sodium hydride [74]. Such an issue was recently addressed by Chua et al [69]. The preparations of sodium and potassium hydrazinidoboranes were performed in an autoclave while using tetrahydrofuran as dispersion medium.…”
Section: Chemical Modification Of Hydrazine Boranementioning
confidence: 99%
“…In isothermal conditions, at 88 °C, potassium hydrazinidoborane was able to liberate 1.8 equivalents of H2 (60% of its theoretical H) within 1 h, whereas hydrazine borane released only 0.5 equivalent of H2 (15% of its theoretical H). Chua et al [69] emphasized the complexity of the dehydrogenation mechanisms. In particular, they suggested that the initial step would be characterized by the formation of dimers like NH2NH(M)BH2-NHNH(M)BH3 and NH2NH(M)BH=NNH(M)BH3 (with M as Li, Na or K) obtained by intermolecular reactions between H δ+ in one molecule and H δ− in another one.…”
Section: Chemical Modification Of Hydrazine Boranementioning
confidence: 99%
“…Specifically, the as-synthesized Ni 421 The hydrogen in N 2 H 4 BH 3 can be released through either thermolysis or solvolysis. [421][422][423][424][425][426][427][428] The thermal decomposition of N 2 H 4 BH 3 was firstly reported by Goubeau and Ricker. 421 N 2 H 4 BH 3 begins to decompose slowly at around 60°C.…”
Section: Metal Np Catalystsmentioning
confidence: 99%